UPAYA MENINGKATKAN HASIL BELAJAR PERKALIAN MELALUI PENGGUNAAN GAMBAR TOKOH PAHLAWAN DENGAN METODE GROUP INVESTIGATION PADA SISWA KELAS III SEMEST 1 SD NEGERI BANDUNGREJO 1 2013/2014 - F.A. Sumardi (Universitas PGRI Semarang, 2014)
Arithmetic skills are often overlooked. The difficulties experienced by students is because teachers often use the lecture method of teaching without the use of appropriate learning media and appropriate. To improve mathematics learning achievement in the subject matter of multiplication, the authors use an image hero by learning methods group investigation. Through the medium of this study are expected to mathematics achievement in simple fractions of material can be improved. The design of this research action research (Action Research) by using the spiral model. The results showed that the use of images hero with the investigation group learning methods can enhance the learning achievement of multiplication in third grade primary school students Bandungrejo 1 Karanganyar District of Demak the 1st half of the school year 2013/2014. This is indicated by the results of the learning improvement obtained average value and completeness increased. The average value before the improvement of learning is then increased to 73.42 66.05 to 80.26 in the first cycle and the second cycle. Percentage of completeness students also increased, where before it was held instructional improvement, the percentage of completeness only 63.00% and then increased to 82.00% in the first cycle and 100% in the second cycle. Pengguanaan hero image with the investigation group learning method can improve students' ability in solving multiplication. Keywords: PTK, multiplication, images, methods of investigation grop Arithmetic skills are often overlooked. The difficulties experienced by students is because teachers often use the lecture method of teaching without the use of appropriate learning media and appropriate. To improve mathematics learning achievement in the subject matter of multiplication, the authors use an image hero by learning methods group investigation. Through the medium of this study are expected to mathematics achievement in simple fractions of material can be improved. The design of this research action research (Action Research) by using the spiral model. The results showed that the use of images hero with the investigation group learning methods can enhance the learning achievement of multiplication in third grade primary school students Bandungrejo 1 Karanganyar District of Demak the 1st half of the school year 2013/2014. This is indicated by the results of the learning improvement obtained average value and completeness increased. The average value before the improvement of learning is then increased to 73.42 66.05 to 80.26 in the first cycle and the second cycle. Percentage of completeness students also increased, where before it was held instructional improvement, the percentage of completeness only 63.00% and then increased to 82.00% in the first cycle and 100% in the second cycle. Pengguanaan hero image with the investigation group learning method can improve students' ability in solving multiplication. Keywords: PTK, multiplication, images, methods of investigation grop